BOHICA - Elving, Wim (Teorija in praksa, 2011)
Within change literature, pace and frequency of organizational change are reoccurring topics. The pace is experienced as high and the frequency of change within organizations appears to be growing exponentially. This lead to study to more extent 'change fatigue' that already received attention in both practice-oriented and scientific literature. Despite this attention, the origin, consequences and implications of change fatigue still remain unclear until today. Lack of acceptation and agreement on the necessity of the change can result in negative attitudes, like 'BOHICA: Bend Over Here It Comes Again'. We constructed a change fatigue instrument that was studied in relation with important aspects of communication change as well on resistance to change and uncertainty. The relevance of this construct can be traced back because of the strong relations we found in this study.
Keywords: Organizacijske spremembe; Organizational change; Communication; Komuniciranje; Empirical analysis; Empirična analiza; podjetja; zaposleni; spremembe; utrujenost